The chancellor and the citadel - Frantz, Maria Capelle, 1996- (Iron Circus Comics, 2018)
The Chancellor rules over a magical city named the Citadel, and keeps the populace safe from the humans outside the city walls. When a group of humans infiltrate the city, the Chancellor wipes them out, and, fearing that humans will destroy the new world just as they did the old, the Citadel descends into aggression. Then it's found out that the Chancellor has spared a human and the Citadel turns against the Chancellor and demand action. The Chancellor's only solace is Olive, who has been using her magic to heal the survivor, but is also aware how dangerous things are for her now that the Chancellor is under attack.